Cognitive Sciences in the Classroom: Toward a Model of Comprehension - Lounis , Zakia (El Omda in Linguistics and Discourse Analysis, 2023)
In this research, we propose to address the activity of text comprehension as a complex cognitive process. We will attempt to provide answers to the following questions: How is this activity organized from a cognitive point of view? And which cognitive processes are involved in text processing? This will be done by reviewing the various studies in cognitive psychology that have, over time, proposed and in some cases refined models of comprehension based on a cognitive theory.